Pemanfaatan Limbah Fly Ash dan Spent Bleaching Earth sebagai Substitusi Semen pada Beton Mutu Normal Skala Produksi - Nababan, Otto Lambok Raya; Iryani, Dewi Agustina; Wahono, Endro Prasetyo; Rinawati, Rinawati (Dampak, 2023)
In the era of industry and technology in Indonesia, environmental problems due to waste are problems that require wise handling. Fly Ash (FA) waste from PLTU activities and Spent Bleaching Earth (SBE) waste resulting from the palm oil production process are very abundant, thus polluting the environment. Indonesia is currently prioritizing physical infrastructure development, which aims to improve connectivity and encourage economic growth in every sector. The development process that occurs increases the use of concrete. Concrete has a tremendous impact on the environment because most of its composition is cement. The use of cement in the manufacture of concrete results in the emission of large amounts of CO2 gas into the atmosphere, which causes an increase in global warming. The use of concrete can have a lower environmental impact if the use of cement is reduced as much as possible by adding a mixture of FA and SBE wastes. This research will utilize FA and SBE waste in the manufacture of normal concrete production weights and aim to determine the optimal composition of FA and SBE waste that is economically and environmentally feasible. The results of the research by applying FA and SBE substitutions show that FA is better than bleaching earth in the resulting compressive strength. The optimal composition of FA as a substitute for cement to achieve the quality of the planned concrete is 15%, while the composition of SBE as a substitute for cement is 10%. Keywords: concrete, Fly Ash (FA), Spent bleaching earth (SBE), concrete compressive strength  ABSTRAK In the era of industry and technology in Indonesia, environmental problems due to waste are problems that require wise handling. Fly Ash (FA) waste from PLTU activities and Spent Bleaching Earth (SBE) waste resulting from the palm oil production process are very abundant, thus polluting the environment. Indonesia is currently prioritizing physical infrastructure development, which aims to improve connectivity and encourage economic growth in every sector. The development process that occurs increases the use of concrete. Concrete has a tremendous impact on the environment because most of its composition is cement. The use of cement in the manufacture of concrete results in the emission of large amounts of CO2 gas into the atmosphere, which causes an increase in global warming. The use of concrete can have a lower environmental impact if the use of cement is reduced as much as possible by adding a mixture of FA and SBE wastes. This research will utilize FA and SBE waste in the manufacture of normal concrete production weights and aim to determine the optimal composition of FA and SBE waste that is economically and environmentally feasible. The results of the research by applying FA and SBE substitutions show that FA is better than bleaching earth in the resulting compressive strength. The optimal composition of FA as a substitute for cement to achieve the quality of the planned concrete is 15%, while the composition of SBE as a substitute for cement is 10%. Kata kunci: beton, Fly Ash (FA), Spent bleaching earth (SBE), kuat tekan beton